Ottoman ghosts and legacies: A drift through the Dead Zone in Cyprus. (October 2019) - Adil, Alev
This creative piece explores traces and erasures of a Cypriot Ottoman heritage by transposing autoethnographic and psychogeographical practice to Europe's southernmost capital, Nicosia. It walks the border zone in Nicosia, once the site of the river Pedios, later a major Ottoman commercial street, a boundary from 1958 to 1974, and since then, a Dead Zone and the internationally contested border between the Republic of Cyprus and the unrecognized Turkish Republic of Northern Cyprus. Photography and writing are presented in conjunction with pages in Ottoman Turkish by my great-grandfather, the poet Imam Mustafa Nuri Effendi, who made a notebook from the English periodical The War Pictorial while incarcerated as an enemy alien in Kyrenia Castle by the British during World War I. I explore how these pages speak of my transcultural Ottoman, Turkish-Greek-Cypriot and English heritages and of changes in Cypriot culture in the century between his war and ours.